MOTHER AND CARRIER: PHENOMENOLOGY STUDY OF DUAL-CARRIER FAMILY - Subhan Ajrin (Kafa`ah: Journal of Gender Studies, 2014)
Mother with dual-career family has a dual role to be performed at the same time. Therefore, as a mother with double plays in a dilemma between family and career interests. Data collection using "snow-ball"  technique to 12 informants and informant election using theoretical sampling. The process of data analysis include braketing, horizonalizing, meaning units to get the description textural, imaginative variation to get the description structural, and blends (composite) into a meaning universal. The results showed that although mothers working face a dilemma in attempting to balance career and family, but for the mother's own career is needs to embodiment her self-and actualization strengthen existence. Their role models, the permission of the husband and the state of children, its potential and the desire to improve family economy, as well as the opportunity to rise to Higher career in work place makes mothers works feel need to work but still retains her role as mother and wife.Keywords : Mother , careers , dual - carrier family and self-actualizationCopyright © 2014 by Kafa`ah All right reservedDOI :  10.15548/jk.v4i1.93